2009
DOI: 10.1007/978-3-642-01222-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Decitabine

Abstract: The pyrimidine analogs, 5-azacytidine (azacitidine, Vidaza) and its deoxy derivative, 5-aza-2'-deoxycytidine (decitabine, Dacogen, are the most widely used inhibitors of DNA methylation which trigger demethylation leading to a consecutive reactivation of epigenetically silenced tumor suppressor genes in vitro and in vivo. Although the antileukemic capacity of decitabine has been known for almost 40 years, its therapeutic potential in hematologic malignancies is still under intensive investigation. Multiple cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 133 publications
1
34
0
Order By: Relevance
“…High levels of DNMT1 expression have been reported in cancer patients who are not responsive to chemotherapy (26). DAC incorporated into DNA covalently binds to DNMT1, leading to the reduction of available DNMT1 protein in cells, which in turn results in DNA demethylation and expression of methylation-silenced genes (28,29). In the present study, we demonstrated that DAC decreased DNMT1 protein expression levels, which was consistent with previous findings.…”
Section: Discussionsupporting
confidence: 92%
“…High levels of DNMT1 expression have been reported in cancer patients who are not responsive to chemotherapy (26). DAC incorporated into DNA covalently binds to DNMT1, leading to the reduction of available DNMT1 protein in cells, which in turn results in DNA demethylation and expression of methylation-silenced genes (28,29). In the present study, we demonstrated that DAC decreased DNMT1 protein expression levels, which was consistent with previous findings.…”
Section: Discussionsupporting
confidence: 92%
“…Unlike other chemotherapy resistance mechanisms, DNA methylation is reversible by demethylating drugs; decitabine is one of the most potent demethylating drugs. Decitabine has been used in clinical trials for hematological and solid malignancies, with the major side effect being transient and manageable myelosuppression [12][15]. We showed from previous studies in a preclinical HNSCC model that decitabine not only inhibits tumor growth, it also treats pain-induced loss of function [16].…”
Section: Introductionmentioning
confidence: 97%
“…1), a DAN methyltransferase inhibitor, possesses anti-cancer activities by inhibiting of DAN methylation, leading to DNA hypomethylation and resulting in gene re-expression and cellular differentiation [1][2][3]. It has been widely used in clinic for the treatment of myelodysplastic syndrome, acute myeloid leukemia and chronic myeloid leukemia [4]. In the last 10 years, it was proposed to combine DNA methyltransferase inhibitors with other agents for the treatment of patients with refractory solid tumor malignancies [4,5].…”
Section: Introductionmentioning
confidence: 99%